Analysis of the Business Environment in Construction Service Industry in DKI Jakarta, Indonesia - Rukun Santoso; Erwin Permana (Institut Ilmu Sosial dan Manajemen STIAMI, 2021)
This study aims to specifically analyze the business environment in the construction service industry in DKI Jakarta, by using an external andinternal dimension factor approach. The dimensions of external factors include several indicators such as political, economic, social and technological indicators. While the internal factor dimensions consist of indicators of corporate culture, corporate structure, and corporate resources. The analysis technique uses Structural Equation Model (SEM) with SmartPLS. The number of samples included 370 leaders of construction service companies in DKI Jakarta. One company is represented by one company leader, either large, medium or small scale company. The results showed that external factors are more dominant than the internal factors in shaping the construction service business environment in DKI Jakarta. It can be understood because as the capital city, DKI Jakarta has a far more complex constellation than other regions. It means that in the case of operating companies in Jakarta, they must be agile in managing the external threats and opportunities. Companies that cannot adapt to the very dynamic climate in the capital with the dramatic competition will not be able to survive.